2013
DOI: 10.1111/jbi.12212
|View full text |Cite
|
Sign up to set email alerts
|

Island biogeography of tropical alpine floras

Abstract: Aim We analysed the effects of alpine area, geographical distance between mountains and isolation due to topography on mountain plant species richness, regional species turnover and patterns of species distribution.Location Equatorial mountains of East Africa, South America and New Guinea. MethodsWe collated lists of alpine species and estimated the extent of alpine area for seven mountains in each geographical region to construct species-area curves. We tested the observed frequency distribution of species am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
105
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 48 publications
5
105
0
6
Order By: Relevance
“…Several studies have shown the relationship between species richness and isolation, both in island ecosystems (Gillespie et al 2013;Karger et al 2014) and mountains (Gehrke and Linder 2014;Sklenář et al 2014). In our case, this relationship is only significant for the endemic element, where high species richness is a result of allopatric speciation after immigration, and suggests that the general patterns can change according to different evolutionary histories.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the relationship between species richness and isolation, both in island ecosystems (Gillespie et al 2013;Karger et al 2014) and mountains (Gehrke and Linder 2014;Sklenář et al 2014). In our case, this relationship is only significant for the endemic element, where high species richness is a result of allopatric speciation after immigration, and suggests that the general patterns can change according to different evolutionary histories.…”
Section: Discussionmentioning
confidence: 99%
“…Climatic conditions in inter Andean plateau are generally drier than the high Andes (MAT = 13.2°C; MAP = 839 mm), with a higher percentage of pastoralism, crops and towns. Despite present‐day threats associated with tourism and population growth, as well as global climate change (Bradley, Vuille, Diaz, & Vergara, ), Ecuadorean Andean lakes and their basins are good representatives of tropical high‐mountain ecosystems and are unique biodiversity reservoirs (Sklenář, Hedberg, & Cleef, ).…”
Section: Methodsmentioning
confidence: 99%
“…Little diversifi cation in the tropical Afroalpine contrasts strongly with fi ndings for the tropical alpine-like Páramo regions of the South American Andes (broadly the northern parts of the Andes; ranging from 10 ° N to 10 ° S; Sklenář et al, 2011 ;Gehrke and Linder, 2014 ;Sklenář et al, 2014 ). Diff erences in in situ speciation between the Páramo and the tropical Afroalpine can be observed in Senecio .…”
Section: Discussionmentioning
confidence: 81%
“…Th ere exists one supported subclade ( S. campanulatus-S. hypsobates ) of the New World 1 clade as sampled by Pelser et al (2007) and expanded by Dušková et al (2010) that contains 14 species predominantly occurring in alpine-like conditions (plus three montane species) of the northern Andes ( Luteyn and Churchill, 1999 ). Altogether, in situ speciation is likely to be higher in the Páramo than in EA for Senecio species because although both alpine-like fl oras are of similar age, species richness in general and within particular clades is higher in the Páramo ( Sklenář et al, 2014 ). High speciation rates were reported for, e.g., Andean Gentianella Moench, Halenia Borkh., Hypericum L., and Lupinus L. ( Kadereit and von Hagen, 2003 ;Drummond et al, 2012b ;Nürk et al, 2013 ).…”
Section: Discussionmentioning
confidence: 91%